A Successive Least Squares Method for Structured Total Least Squares (Journal of Computational Mathematics, 2003)
A new method for Total Least Squares (TLS) problems is presented. It differs from previous approaches and is based on the solution of successive Least Squares problems. The method is quite suitable for Structured TLS (STLS) problems. We study mostly the case of Toeplitz matrices in this paper. The numerical tests illustrate that the method converges to the solution fast for Toeplitz STLS problems. Since the method is designed for general TLS problems, other structured problems can be treated similarly.
Keywords: Structure total least squares; Linear least squares; Successive linear squares method; Toelitz systems; Structure least squares.